Comprehending customer satisfaction with hotels: Data analysis of consumer-generated reviews. Issue 5 (14th April 2020) - Li, Hongxiu; Liu, Yong; Tan, Chee-Wee; Hu, Feng
Abstract : Purpose: Building on the three-factor theory, this study aims to unravel how the role of hotel attributes such as basic, excitement and performance factors could differ in accordance with different hotel star ratings and distinct customer segments. Design/methodology/approach: This study explores the asymmetric effects of hotel attributes on customer satisfaction by extracting 412, 784 consumer-generated reviews from TripAdvisor across different cities in China. Findings: By taking into account the origins of customers and hotel star ratings, the study uncovers that guests' expectations of hotel performance differ with respect to their origins (domestic and international guests) and the star ratings of the hotels being reviewed, thereby moderating the asymmetric impact of hotel attributes on customer satisfaction. Research limitations/implications: The study compares and contrasts the determinants of customer satisfaction for domestic and international guests in the context of Chinese hotels. Care should still be exercised when generalizing the insights gleaned from this study to other contexts. Practical implications: The findings from this study translate into actionable guidelines for hotel operators to make informed decisions regarding service improvement. Originality/value: The study extends previous work by offering a deeper understanding of the asymmetric impact of hotel attributes on customer satisfaction. Specifically, this study provides a deep understanding of the different hotel attributes such as basic, performance and excitement factors in explaining customer satisfaction among different hotel customer segments. Findings from this study can not only inform hotel operators on the significance of various hotel attributes in determining customer satisfaction but also guide the formulation of business strategies to retain customers by inducing delight and not frustration.